2022
DOI: 10.4236/jtr.2022.101004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Pulmonary Tuberculosis Diagnosis Delays in Mali a West-African Endemic Country

Abstract: Background: Tuberculosis was the deadliest infectious agent before covid-19; 1.5 million deaths in 2020. Despite, a variety, of easy and cheap diagnostic tools, detection rates still fall below 90%; diagnosis delays are long exceeding 30 days in many continents. This study aimed to determine risk factors for pulmonary TB diagnosis delays in Mali. Methods: A cross-sectional study was conducted in Bamako to include pulmonary TB patients at treatment initiation centers. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…African studies reported prevalence of 61% in Nigeria in 2012 [ 11 ] and 48% in Zimbabwe in 2014 [ 12 ]. A cross-sectional study in Bamako, Mali reported the median patient delay of TB treatment was 58 days [ 13 ]. Over half (56.3%) of all involved patients delay in seeking health care for more than 30 days after the onset of their TB symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…African studies reported prevalence of 61% in Nigeria in 2012 [ 11 ] and 48% in Zimbabwe in 2014 [ 12 ]. A cross-sectional study in Bamako, Mali reported the median patient delay of TB treatment was 58 days [ 13 ]. Over half (56.3%) of all involved patients delay in seeking health care for more than 30 days after the onset of their TB symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning factors associated with patient delay in TB treatment, low income, rural residency, unemployment, old age, and female sex, distance to the DOTs centers, low education level, social reasons and non-request of health workers were the associated factors of patient delay in TB treatment [ 13 , 24 , 25 ]. Factors like lack of knowledge, fear and embarrassment of receiving TB diagnosis, patient tendency to get self-treatment before seeking formal medical care, use of dispensary and private health facilities, employed individuals, secondary-level education and tertiary education, body mass index (BMI) status were also reported as risk factors of patient related TB treatment delay in other settings [ 15 , 18 , 26 ].…”
Section: Introductionmentioning
confidence: 99%